Research on ACEI of Low-Molecular-Weight Peptides from Hirudo nipponia Whitman - Zhao Ding; Keli Chen; Yunzhong Chen (Molecules, 2022)
The renin-angiotensin system (RAS) is the primary pathway for regulating blood pressure in the body, and angiotensin-converting enzymes (ACEs) play a crucial role in it. Hirudo nipponia is an invertebrate that contains a variety of active peptides; however, there are no studies on the ACE inhibitory activity of hirudo. In the present study, our aim was to identify the active peptides in hirudo based on active peptide database analysis, unexpectedly filling the gap in hirudo ACE inhibitory activity research. Prep-HPLC was used to separate the part below 3 kD from hirudo. The peptide composition of the isolates was obtained based on Orbitrap LC-MS. The activity of each group of peptides was predicted by the database and the activity was determined by bioassay. Peptides with validation activity were screened through the database. In total, 337 peptides and 18 peptides matching the NCBI leech protein database were identified. All four fractions showed ACE inhibitory activity, and the IC50 was 0.8266, 0.2708, 0.4432, and 0.1764 mg/mL, respectively. Six screened peptides showed good affinity for ACE. This work reveals for the first time that low-molecular-weight peptides from H. nipponia have ACE inhibitory activity, which can provide a new explanation for leech treatment of hypertension.